УПРАВЛЕНЧЕСКИЙ ПОТЕНЦИАЛ НАЦИОНАЛЬНОЙ ЭКОНОМИКИ: РАМКИ ТЕОРЕТИЧЕСКОГО АНАЛИЗА (Journal of Economic Research & Business Administration, 2015)
The article is devoted for study different approaches to one of the important exponent – management potential, which is characterized conditions and level of development of national economy management system. Besides, in the article there are submission for consideration of problems, which is connected with essence and structure of management potential’s definition and using of basic components of management potential in the scale of republic, region and each separate company.